Editorial: Greenhouse gas measurements in underrepresented areas of the world - Pérez Quezada, J.F.; Meijide, A.; Leitner, Sonja (Frontiers Media, 2023)
Major efforts for quantifying greenhouse gas (GHG) production and consumption in agricultural and natural ecosystems and understanding their drivers are currently being developed around the world, as well as on how climate change will influence ecosystem functioning and with that GHG emissions. These efforts include the monitoring of GHG fluxes with both manual and continuous measurements, mainly with closed soil-atmosphere flux chambers and micrometeorological approaches such as the eddy covariance technique, but also with other methods such as animal respiration chambers. These measurements can be used for calibrating models that simulate ecosystem functioning and their responses to climate change and to estimate local, regional or global GHG budgets. Despite these efforts, there is a large spatial concentration of GHG flux measurements in developed countries, while low- and middle-income countries (LMICs) are underrepresented. As a result, the tropics and most Southern Hemisphere biomes are heavily underrepresented in flux networks (1, 2). At the same time, LMICs are regions with fast population growth and land-use change, thereby potentially creating critical uncertainties in national and global GHG budgets.